2011
DOI: 10.19030/jber.v7i1.2253
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Religion On Remittances Sent To Relatives And Friends Back Home

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-layout-grid-align: none;"><span style="color: black; font-size: 10pt;"><span style="font-family: Times New Roman;">Using The Pilot for the New Immigrant Survey (NIS-P), a nationally representative sample of new legal immigrants to the United States, this paper examines how religiosity influences immigrants&rsquo; remitting behavior. Our analysis addresses two related questions. First, do immigrants from different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
5
2
Order By: Relevance
“…Several studies have also revealed that religion is a determinant of the remittance motive (Kelly & Solomon 2009) but this was not a significant factor in this study, although the descriptive statistics showed a moderate impact (Table 4.43). However, many of the respondent households contributed to their religious institutions irrespective of whether the households were Muslim or Hindu.…”
Section: Source: Developed For This Studycontrasting
confidence: 62%
See 1 more Smart Citation
“…Several studies have also revealed that religion is a determinant of the remittance motive (Kelly & Solomon 2009) but this was not a significant factor in this study, although the descriptive statistics showed a moderate impact (Table 4.43). However, many of the respondent households contributed to their religious institutions irrespective of whether the households were Muslim or Hindu.…”
Section: Source: Developed For This Studycontrasting
confidence: 62%
“…Ellison (1991) have found a strong positive relationship between religious practice by the migrant and remittances. Similarly, Kelly and Solomon (2009) have found a link between religion and altruistic motivation to remit.…”
Section: Characteristics Of Householdmentioning
confidence: 86%
“…Another type, the insurance motive, attributes remittances to a mutual risk diversification arrangement between the migrant and their household (Stark and Levhari 1982;Rosenzweig 1988). A third type, the investment motive, considers remittances a repayment for past loans from the household (Lucas and Stark 1985;Poirine 1997;Kelly and Solomon 2009). Past studies have also looked at the relationship between remitting behaviors and social status attainment (Mountz and Wright 1996;Goldring 2002;Sana 2005;VanWey, Tucker, and McConnell 2005;Cohen 2011;Mahmud 2016), but they have not addressed the issue of who provides social status rewards.…”
Section: Remittances and Immigrant Transnationalismmentioning
confidence: 99%
“…Questions about motivations are central in the remittances literature, where identifying the degree to which altruism or self-interest is a driving force has been an important quest (Lucas and Stark 1985). Yet, although with some exceptions (such as Bashir 2014;Erdal 2012;Kelly and Solomon 2011;Pollard et al 2015), studies on remittances rarely explicitly mention religion. Often there is an implicit assumption about 'ethnic' motivations to help 'one's own' (Sinatti and Horst 2015) in studies on migrant development engagements.…”
Section: Conceptualizing Transnational Islamic Charity As Everyday Rimentioning
confidence: 99%